The Importance of Breakfast Habits for the Activeness of Children Aged 5-6 Years - Theodorina Novyani Seran; Marta o. Bailaen (Early Childhood Education Development and Studies (ECEDS), 2023)
This research sought to find out the importance of breakfast habit on the activeness of children aged 5-6 years. This research was conducted in Hindu Saraswati Kindergarten of Kupang. The research subjects were parents and teachers in Hindu Saraswati Kindergarten of Kupang. The research data were collected through interview and documentation techniques, and then analyzed descriptively. From the results of this research regarding the importance of breakfast habit on the activeness of children aged 5-6 years in Hindu Saraswati Kindergarten of Kupang, it was revealed that breakfast is very important for the activeness of children aged 5-6 years. Children who eat breakfast are more active in doing all their activities. Their activeness can be seen from several aspects, including courage, participation, creativity, and independence.